Drug Decriminalization and the Price of Illicit Drugs - Sónia Félix; Pedro Portugal (Institute for the Study of Labor (IZA), 2015)
This study is an empirical assessment of the impact of the drug decriminalization policy followed by Portugal in July, 2001. We investigate especially the impact of the policy change on the price of illicit drugs. The analysis is performed using a difference-in-differences approach and a comprehensive set of countries as control group. We also investigate the application of Synthetic Control Method in order to construct a synthetic control unit from a convex combination of other countries. The results suggest that the prices of opiates and cocaine in the post-treatment period did not decrease in the sequence of the policy change. This result contrasts with the argument that softer drug law enforcement necessarily leads to lower prices and, consequently, to higher drug usage rates and dependence.
Keywords: C21; D04; 330; illicit drugs; drug decriminalization policy; drug prices; treatment effects